Serum vitamin C levels in goats with Peste des Petits Ruminants (PPR) - Issi, M; Gül, Y; Dabak, M (Tubitak Scientific & Technological Research Council Turkey, 2001)
The role of Vitamin C in the medical treatment of Peste des Petits Ruminants (PPR) was investigated by measuring the serum vitamin C levels in goats with PPR. Fifteen goats 5-6 months old with PPR (sick group) and 15 healthy goats 9-10 months old (control group) were used. All the animals used in the study were systematically and clinically examined and blood samples were obtained for white blood cell counts and serum Vitamin C levels. The white blood cell counts were detected using Thoma microslides. Serum Vitamin C levels were measured by the phosphotungstic acid method with Schimadzu UV-1208, UV-VIS Spectrophotometer. The differences in average body temperature, respiration rate, rumen activity and serum vitamin C levels of the animals in the control group and sick group was found to be significant (p < 0.001) and also a significant difference between the groups was found in terms of pulse rate and white blood cell counts (p < 0.01). In conclusion, because of the low serum Vitamin C levels in animals with PPR, administration of vitamin C appears to be useful for increasing body resistance and for activation of the immune defence system.
Küçük Ruminant Vebasi Saptanan Keçilerde Serum Vitamin C Düzeyleri
Keywords: Peste des Petits ruminants; vitamin C